Malleability of spatial skills: bridging developmental psychology and toy design for joyful STEAM development - İleri, Çiğdem İrem; Erşan, Melisa; Kalaça, Duru; Coşkun, Aykut; Göksun, Tilbe; Küntay, Aylin C. (Frontiers in Psychology, 2023)
Previous research has established that advances in spatial cognition predict STEAM success, and construction toys provide ample opportunities to foster spatial cognition. Despite various construction toy designs in the market, mostly brick-shaped building blocks are used in spatial cognition research. This group of toys is known to enhance mental rotation; however, mental rotation is not the only way to comprehend the environment three-dimensionally. More specifically, mental folding and perspective taking training have not received enough attention as they can also be enhanced with the construction toys, which are framed based on the 2×2 classification of spatial skills (intrinsic-static, intrinsic-dynamic, extrinsic-static, extrinsic-dynamic). To address these gaps, we compile evidence from both developmental psychology and toy design fields to show the central role played by mental folding and perspective taking skills as well as the importance of the variety in toy designs. The review was conducted systematically by searching peer reviewed design and psychology journals and conference proceedings. We suggest that, over and above their physical properties, construction toys offer affordances to elicit spatial language, gesture, and narrative among child-caregiver dyads. These interactions are essential for the development of spatial skills in both children and their caregivers. As developmental psychology and toy design fields are two domains that can contribute to the purpose of developing construction toys to boost spatial skills, we put forward six recommendations to bridge the current gaps between these fields. Consequently, new toy designs and empirical evidence regarding malleability of different spatial skills can contribute to the informal STEAM development.